The prevalence of cardiac complications and their impact on outcomes in patients with non-traumatic subarachnoid hemorrhage - Lång Maarit; Jakob Stephan M.; Takala Riikka; Lyngbakken Magnus N.; Turpeinen Anu; Omland Torbjörn; Merz Tobias M.; Wiegand Jan; Grönlund Juha; Rahi Melissa; Valtonen Mika; Koivisto Timo; et al. (NATURE PORTFOLIO, 2025)
Subarachnoid hemorrhage (SAH) is a serious condition, and a myocardial injury or dysfunction could contribute to the outcome. We assessed the prevalence and prognostic impact of cardiac involvement in a cohort with SAH. This is a prospective observational multicenter study. We included 192 patients treated for non-traumatic subarachnoid hemorrhage. We performed ECG recordings, echocardiographic examinations, and blood sampling within 24 h of admission and on days 3 and 7 and at 90 days. The primary endpoint was the evidence of cardiac involvement at 90 days, and the secondary endpoint was to examine the prevalence of a myocardial injury or dysfunction. The median age was 54.5 (interquartile range [IQR] 48.0–64.0) years, 44.3% were male and the median World Federation of Neurological Surgeons (WFNS) score was 2 (IQR 1–4). At day 90, 22/125 patients (17.6%) had left ventricular ejection fractions ≤ 50%, and 2/121 patients (1.7%) had evidence of a diastolic dysfunction as defined by mitral peak E-wave velocity by peak eʹ velocity (E/eʹ) > 14. There was no prognostic impact from echocardiographic evidence of cardiac complications on neurological outcomes. The overall prevalence of cardiac dysfunction was modest. We found no demographic or SAH-related factors associated with 90 days cardiac dysfunction.